The relationship between intake of fruits, vegetables and dairy products with overweight and obesity in a large sample in Iran: Findings of STEPS 2016 - Nouri, Mehran; Shateri, Zainab; Faghih, Shiva (Frontiers in Nutrition, 2023)
Background The present study aimed to investigate the association between fruits and vegetables (FVs) and dairy product intake with body weight based on the data from the nationwide Stepwise approach to surveillance (STEPS) survey in Iran. Methods STEPS is a national-based cross-sectional study conducted on 3,0541 people selected by stratified cluster random sampling in Iran from April to November 2016. The outcome of the current study was body mass index (BMI) which was classified as normal weight, underweight, overweight, and obese. Also, as exposure variables, dietary intakes of fruits, vegetables and dairy products were extracted from the STEPS questionnaires. Multinomial logistic regression was used to evaluate the association between dairy products, FVs consumption, and BMI category in the crude and adjusted models. Results In the adjusted model, we observed 41% [odd ratio (OR) = 0.59; 95% confidence intervals (CI): 0.50, 0.68, P < 0.001], 27% (OR = 0.73; 95% CI: 0.62, 0.84, P < 0.001), and 26% (OR = 0.74; 95% CI: 0.63, 0.87, P < 0.001) lower odds of being overweight, and 46% (OR = 0.54; 95% CI: 0.46, 0.64, P < 0.001), 29% (OR = 0.71; 95% CI: 0.60, 0.84, P < 0.001), and 21% (OR = 0.79; 95% CI: 0.65, 0.95, P = 0.014) decrease in obesity odds among the participants who consumed 1, 2, and more than 2 servings of fruits per day in comparison to less than one serving, respectively. Also, we observed participants who consumed 1, 2, and more than 2 servings in comparison to less than one serving of dairy products per day had 31% (OR = 0.69; 95% CI: 0.58, 0.81, P < 0.001), 23% (OR = 0.77; 95 %CI: 0.65, 0.91, P = 0.002), and 21% (OR = 0.79; 95% CI: 0.67, 0.94, P = 0.011) lower odds of being overweight and 47% (OR = 0.53; 95% CI: 0.44, 0.64, P < 0.001), 36% (OR = 0.64; 95% CI: 0.53, 0.77, P < 0.001), and 32% (OR = 0.68; 95% CI: 0.56, 0.83, P < 0.001) lower odds of obesity, respectively. In addition, compared to participants who consumed less than 2 servings of vegetables per day, participants who consumed 2, 3, and more than 3 servings had 40% (OR = 0.60; 95% CI: 0.47, 0.76, P < 0.001), 29% (OR = 0.71; 95% CI: 0.56, 0.90, P = 0.006), and 26% (OR = 0.74; 95% CI: 0.57, 0.96, P = 0.027) lower odds of being overweight, respectively. Furthermore, we observed 36% lower odds of obesity among participants who ate 2 servings of vegetables per day compared to less than 2 serving (OR = 0.64; 95% CI: 0.49, 0.84, P = 0.002). Conclusion Our findings showed that intake of FVs and dairy products is associated with a healthier weight status in adults. Further studies are needed to confirm these findings.